Simulation for communication skills training in medical students: Protocol for a systematic scoping review. (2019) - Bakogiannis, Angelos; Darling, Jonathan C.; Dimitrova, Vania; Roberts, Trudie E.; ,
Abstract: Empirical research has produced inconclusive, and occasionally contradictory, evidence relating to the extent to which improvements in medical communication skills taught through simulation can be measured. This is further limited by the wide range of designs and outcome collection methods that studies employ and does not allow for data comparability or meta-analysis. The proposed scoping review aims to systematically map and comprehensively explore the extent, range and nature of research activity on the use of simulation for communication skills training in medical education. Comprehensive literature searches in MEDLINE, EMBASE, Scopus and Web of Science will be performed and data will be reported using quantitative (simple numeric counts) and qualitative (thematic synthesis) analyses.